Correlations Between the Opioid System, Imidazoline Receptors, and EEG: An Investigation of Acquired Drug-Seeking Behaviors in Different Environments - Gabriela Rusu-Zota; Dan Trofin; Cristina Gales; Elena Porumb-Andrese (Applied Sciences)
The investigation of the reward system is a fascinating domain with future applications for pain therapy and understanding addiction. We investigated interactions between tramadol use and the imidazoline system, through the modulatory effects of imidazoline receptor blockers, by behavior analysis and electroencephalography (EEG). Thirty-six male Wistar rats were placed within a conditioned place preference (CCP) setting using a three-compartment box apparatus. The transition of the six groups of subjects from one compartment to another was constantly monitored, related to preconditioning for one day, conditioning for eight days, and post-conditioning testing on day 10. During the conditioning phase, the groups received: a saline solution, efaroxan, idazoxan, tramadol, tramadol + efaroxan, and tramadol + idazoxan, respectively. The administration of efaroxan, idazoxan, or a saline solution in the non-preferred compartment did not alter the time spent by rats there. On the other hand, the administration of tramadol alone in the non-preferred compartment significantly increased the time spent by animals there (151.66 ± 11.69 s) post-conditioning as compared to preconditioning (34.5 ± 5.31 s) (p < 0.01), while the combination of efaroxan and tramadol significantly reduced its effect. After the combination with idazoxan, the effect of tramadol on increasing the time spent by the animal in the non-preferred compartment remained significantly higher than in the preconditioning phase. A significant increase in time spent in the non-preferred compartment demonstrates the existence of a CPP induction effect (by changing the preference). The effects of tramadol on the reward system can cause changes in the brain’s neuroplasticity, potentially leading to learned behaviors that promote drug seeking in previous non-preferred environments.